2022
DOI: 10.1111/evj.13605
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genetic characteristics of Cryptosporidium spp. in Chinese racehorses

Abstract: Background: Cryptosporidium is a protozoan parasite causing diarrhoea in humans and animals. Although Cryptosporidium has been found in domestic horses (farmed or kept at pasture), there has been only one published study of Cryptosporidium infections in Chinese racehorses, which was restricted to a very small geographical area.Objectives: To investigate the presence of Cryptosporidium spp. in the faeces of racehorses in China and to perform molecular characterisation of the parasite. Study design: Cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
1
8
2
Order By: Relevance
“…Studies from China that used polymerase chain reaction (PCR) to investigate Cryptosporidium spp. prevalence in adult horses reported an average prevalence of 1.8-3.1%(Li, et al 2019, Qi et al 2015, Xu, et al 2022) which is much lower than the prevalence reported here. A recent systematic review and meta-analysis reported a pooled prevalence of 13.8% from studies that used microscopy compared with only 4.7% from studies that used PCR (Hatam-Nahavandi, et al 2019).…”
contrasting
confidence: 62%
See 4 more Smart Citations
“…Studies from China that used polymerase chain reaction (PCR) to investigate Cryptosporidium spp. prevalence in adult horses reported an average prevalence of 1.8-3.1%(Li, et al 2019, Qi et al 2015, Xu, et al 2022) which is much lower than the prevalence reported here. A recent systematic review and meta-analysis reported a pooled prevalence of 13.8% from studies that used microscopy compared with only 4.7% from studies that used PCR (Hatam-Nahavandi, et al 2019).…”
contrasting
confidence: 62%
“…Other limitations of the current study were that samples were collected at a single time point and therefore we did not consider intermittent shedding of Cryptosporidium spp. oocysts (Xu, et al 2022) which might have underestimated the prevalence reported. Furthermore, neither locations nor horses were randomly selected to be included in the current study which might limit the generalisability of our results.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations